1991
DOI: 10.1037/0735-7028.22.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of persons with multiple sclerosis, with an emphasis on what is needed from psychologists.

Abstract: A sample of 125 persons having had multiple sclerosis (MS) for an average of 16.5 years completed a battery of self-report tests assessing current behavioral and emotional functioning and mental health needs. The resulting data contradicted the stereotype many psychologists hold of persons with MS by consistently indicating that most of these persons had adapted successfully to having the disease. Those who had not successfully adapted expressed a need for help with two matters in particular: accepting the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Yet some studies purporting to examine the role of roles and occupations in maintaining subjective quality of life with MS only measure the frequency of participation in different activities by people with MS rather than their personal value and meaning (Eklund & MacDonald, 1991;Finlayson, Impey, Nicolle, & Edwards, 1998;Lundmark & Branholm, 1996). Therefore this study not only explores emotional and cognitive coping strategies but seeks to understand women's wider strategies for living an acceptable life in the context of 6 MS. Special consideration is given to the roles and occupations that fill daily life in satisfying ways.…”
Section: Study Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Yet some studies purporting to examine the role of roles and occupations in maintaining subjective quality of life with MS only measure the frequency of participation in different activities by people with MS rather than their personal value and meaning (Eklund & MacDonald, 1991;Finlayson, Impey, Nicolle, & Edwards, 1998;Lundmark & Branholm, 1996). Therefore this study not only explores emotional and cognitive coping strategies but seeks to understand women's wider strategies for living an acceptable life in the context of 6 MS. Special consideration is given to the roles and occupations that fill daily life in satisfying ways.…”
Section: Study Purposementioning
confidence: 99%
“…Eklund & MacDonald 1991;Finlayson et al 1998;Lundmark & Branholm 1996) but there is little information about ways in which people preserve or extend their activities. This study uncovered a wide range of leisure and voluntary activities.…”
mentioning
confidence: 99%
“…Er zijn aanwijzingen, dat de mate waarin de zieke er in slaagt zich aan veranderende omstandigheden aan te passen (Brooks & Matson, 1982) en een positief en optimistisch zelfbeeld te behouden (Fournier, De Ridder en Bensing, 1999) van grote invloed is op de ervaren kwaliteit van leven. De mogelijkheden om zelf invloed uit te oefenen op het verloop van de ziekte en op de symptomen ervan zijn echter zeer beperkt en patie¨nten moeten leren te leven met de onzekerheid van het beloop van de ziekte, de symptomen en de psychosociale gevolgen (Eklund & Mac Donald, 1991). ADL-functies worden verstoord, het relatiesysteem vereist aanpassing, de beroepsuitoefening wordt onzeker en het seksueel functioneren en het gezinsleven kunnen veranderen.…”
Section: Inleidingunclassified
“…The characteristics of multiple sclerosis may also lead those diagnosed to seek counseling because of psychological difficulties that either are a symptom of the disease or are a result of adjusting to and/or coping with the disease. In one study, 58% of persons with multiple sclerosis believed that they needed professional help for their emotional problems, although nearly half of those reported that they were not receiving such assistance (Eklund & MacDonald, 1991). A more recent study found that persons with multiple sclerosis have a need for mental health interventions at more than 2.6 times the rate of those in the general population (Patten, Beck, Williams, Barbui, & Metz, 2003).…”
mentioning
confidence: 97%